Hydrolysis of Jatropha curcas oil for biodiesel synthesis using immobilized Candida cylindracea lipase - Kabbashi, Nassereldeen Ahmed; Mohammed, Nurudeen Ishola; Mirghani, Mohamed Elwathig Saeed; Alam, Md Zahangir (Elsevier B.V., 2015)
Environmental degradation and the diminishing reserves of fossil fuel are the major drives for the searchfor biodiesel as alternative fuel. Jatropha curcas oil has been well researched as non-edible vegetableoil for the production of biodiesel using conventional processes which generate huge obnoxious wastesand consequently incur additional cost for treatment and disposal of the generated waste. This paperpresents the hydrolytic biosynthesis of J. curcas hydrolysate (FFA) for the production of biodiesel usinglocally produced Candida cylindracea lipase immobilized on functionalized activated carbon support. Upto 78% of free fatty acid (FFA) was achieved through hydrolytic reaction relative to the source and activityof the enzyme employed. Optimum dose of the catalyst loading was 8% (w/w) of the immobilized matrixat 40◦C reaction temperature and 200 rpm agitation. All reactions were allowed to proceed for 24 h, andcatalyst could be recycled four times for optimal FFA yield.